Sinterability of Magnesium Hydroxyapatite Bioceramic and Its Mechanical Properties - Ramli, Syakir; Che Murad, Mardziah; Rozlin Nik Masdek, Nik (International Journal of Engineering and Technology, 2018)
One of the most favoured material in bone tissue engineering field nowadays is hydroxyapatite (HA), which is also known to be bioactive and has a similar composition to human bone. However, developing an artificial bone or bone graft using biocompatible HA is a challenging task due to the lower strength of the main substance. To improve the mechanical properties of synthetic HA, introduction of metallic substance such as magnesium (Mg) into HA has been proposed. In this present study, 0, 10 15 wt% of magnesium hydroxyapatite (MgHA) nanopowders were prepared by a simple wet precipitation method. These nanopowders were then compacted using a 10-ton compression uniaxial press machine with 150 MPa pressure to form a disc shape of dense MgHA. After that, the MgHA discs were sintered at a temperature of 1000 °C and 1100 °C to remove the organic compounds and further densify the ceramics. XRD results showed that the crystallinity of MgHA increased when the sintering temperature increases. The compression test showed that the 10 wt% MgHA sample recorded the highest compressive strength (243.59 MPa) when sintered at 1100 °C, while pure HA has the lowest value with 49.37 MPa. This study also demonstrates that sintering temperature at 1100 °C gives significant improvement to the mechanical properties of the MgHA dense bodies compared to sintering at 1000 °C.